Pantoea agglomerans in Immunodeficient Patients with Different Respiratory Symptoms - Erika Odilia Flores Popoca; Maximino Miranda García; Socorro Romero Figueroa; Aurelio Mendoza Medellín; Horacio Sandoval Trujillo; Hilda Victoria Silva Rojas; Ninfa Ramírez Durán (The Scientific World Journal)
The aim of this paper was to determine in 32 patients from 4 different Mexican hospitals the frequency of opportunistic bacteria in the 2010 to 2011 time period. The patients were divided in 4 groups. Group 1 included 21 HIV positive patients with acute respiratory syndrome. Four HIV positive patients with tuberculosis symptoms were included in Group 2; two patients with tuberculosis symptoms and one asymptomatic person formed Group 3. Reference Group 4 included 4 patients from whom 4 strains of Mycobacterium spp. had been reported. The strains were isolated and identified by 16S rRNA gene amplification, API 20E and 50CH, biochemical test, and antibiotic sensitivity. The strains found were 10 Pantoea agglomerans, 6 Mycobacterium spp., 6 Pseudomonas spp. and 10 strains of normal floral species: Thermoactinomycetes bacterium (1), Enterococcus faecium (2), Bacillus licheniformis (1), Lactobacillus rhamnosus (2), Streptococcus oralis (2), Streptococcus anginosus (1), and Enterobacter hormaechei (1).